Defining potential roles of Pb2+ in neurotoxicity from a calciomics approach. Issue 6 (25th April 2016) - Gorkhali, Rakshya; Huang, Kenneth; Kirberger, Michael; Yang, Jenny J.
Abstract : Metal ions play crucial roles in numerous biological processes, facilitating biochemical reactions by binding to various proteins. Abstract : Metal ions play crucial roles in numerous biological processes, facilitating biochemical reactions by binding to various proteins. An increasing body of evidence suggests that neurotoxicity associated with exposure to nonessential metals ( e.g., Pb 2+ ) involves disruption of synaptic activity, and these observed effects are associated with the ability of Pb 2+ to interfere with Zn 2+ and Ca 2+ -dependent functions. However, the molecular mechanism behind Pb 2+ toxicity remains a topic of debate. In this review, we first discuss potential neuronal Ca 2+ binding protein (CaBP) targets for Pb 2+ such as calmodulin (CaM), synaptotagmin, neuronal calcium sensor-1 (NCS-1), N -methyl-d -aspartate receptor (NMDAR) and family C of G-protein coupled receptors (cGPCRs), and their involvement in Ca 2+ -signalling pathways. We then compare metal binding properties between Ca 2+ and Pb 2+ to understand the structural implications of Pb 2+ binding to CaBPs. Statistical and biophysical studies ( e.g., NMR and fluorescence spectroscopy) of Pb 2+ binding are discussed to investigate the molecular mechanism behind Pb 2+ toxicity. These studies identify an opportunistic, allosteric binding of Pb 2+ to CaM, which is distinct from ionic displacement. Together, these data suggest three potential modes of Pb 2+ activity related to molecular and/or neural toxicity: (i) Pb 2+ can occupy Ca 2+ -binding sites, inhibiting the activity of the protein by structural modulation, (ii) Pb 2+ can mimic Ca 2+ in the binding sites, falsely activating the protein and perturbing downstream activities, or (iii) Pb 2+ can bind outside of the Ca 2+ -binding sites, resulting in the allosteric modulation of the protein activity. Moreover, the data further suggest that even low concentrations of Pb 2+ can interfere at multiple points within the neuronal Ca 2+ signalling pathways to cause neurotoxicity.